Full and Partial State Discontinuous Integral Control. Issue 13 (2018) - Mercado-Uribe, Angel; Moreno, Jaime A.
Abstract: Homogeneous Discontinuous Integral Controllers are very effective to track or regulate a reference signal and to reject perturbation signals, which are Lipschitz continuous. This is in contrast to Continuous Integral Controllers, which are able to track and reject only constant signals. In this paper we extend some recent results, attained for systems with relative degree two, to relative degree three. We develop a Lyapunov based analysis and design method, that is able to be extended to an arbitrary relative degree, and that allows a differentiate design for Integral controllers depending on the full or a partial state.